Supporting factors of IT business alignment at Indonesian it companies - Clara Hetty Primasari; Djoko Budiyanto Setyohadi (Universitas 'Aisyiyah Yogyakarta, 2022)
Aligning IT with business strategies is the focus of attention of many IT and business leaders and managers. Many previous researchers have examined how to obtain or achieve this alignment. From that research we know, the Strategic Alignment Model, Integrated Architecture Framework, Luftman's Alignment Model, Reich Benbasat Model, and other alignment models. However, most of the above studies were carried out in countries in the Americas. The difference in geographical location, culture, population and countries where the research is carried out influences on how companies in these countries achieve alignment. This study aims to determine the supporting factors of IT Business alignment of companies in Indonesia, especially in Yogyakarta. The study is based on the SAM model introduced by Henderson and Venkatraman and conducted with in-depth interviews with three companies in Yogyakarta followed by an analysis of the results of the interview. From this study, obtained factors supporting the alignment of IT and business from companies, among others: Products support Distinctive Competencies, Manager support supports Distinctive Competencies, Manager’s softskill supports Distinctive Competencies, Vision and Mission statements support Business Scope, Partnership supports Business Scope, and Partnership supports the Organizational Process.